Umkämpfte Wirtschaften: Kaffeehandel, europäische Einwanderung und die zentralamerikanischen Ökonomien im Ersten Weltkrieg - Berth, Christiane (Anuario de Historia de América Latina, 2018)
The article discusses how the First World War affected the Central American economies mainly dependent on the export of coffee and bananas. As European immigrants played a key role in the coffee business, the article also analyzes changes in their trade networks. During the war years, conflicts existed on three levels: first, the U.S. and European powers struggled for economic influence in the region. Second, diplomats tried to exploit immigrants for their political purposes which led to tensions. Third, the Central American governments attempted to use the global conflict for their own economic interests. However, their scope was small as the Central American countries produced no strategic raw materials for war. Deteriorating coffee prices and local currencies losing value affected the regional economy. After Britain and the U.S. established Black Lists with enemy firms between 1915 and 1917, companies had to (re)define their national belonging. Given the strong presence of immigrants and the international trade networks this was a difficult task. Some firms tried to demonstrate a neutral profile, while others eliminated German partners from their business. Finally, the US expropriated German firms in Guatemala and Honduras. However, most businesses were returned to former owners around 1920. In the following decade, the US and Germany competed again for economic influence in Central America.
Keywords: Economy; Central American History; Trade Networks; Migration